2010
DOI: 10.3743/kosim.2010.27.4.071
|View full text |Cite
|
Sign up to set email alerts
|

The Study on the Research Trend of Social Network Analysis and the its Applicability to Information Science

Abstract: In this study, we analyzed the research trend of social network analysis. We investigated how this topic can be linked to the information science. We analyzed 163 articles that were retrieved from searching "social network analysis" in the keyword search field from 2000 to 2009. The study revealed the fast growth of the research of social network analysis in recent years. Also, the study showed that social network analysis has been applied to many cognate disciplines including management science, education sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…It is represented by a line in the network. Density, centrality and centralisation are the most widely used indices in network analyses (Kim, 2011;Kim and Chang, 2010). Centrality describes the extent to which a node is located centrally in the entire network.…”
Section: Social Network Analysismentioning
confidence: 99%
“…It is represented by a line in the network. Density, centrality and centralisation are the most widely used indices in network analyses (Kim, 2011;Kim and Chang, 2010). Centrality describes the extent to which a node is located centrally in the entire network.…”
Section: Social Network Analysismentioning
confidence: 99%
“…This methodology can introduce research that represents a defined scope and identifies the most impactful study in the scope of the field. The rapid growth of research using social network analysis in the early 2000s demonstrated this application embedded in bibliometrics and webmetrics [39]. The study of research trends using a keyword network analysis was used to understand literature in the huge quantitative scale.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this rise is that this application domain offers a particularly fertile place to test and develop advanced computational techniques to extract valuable information from networks. SNA has been widely used in diverse fields such as economic geography (Ter Wal and Boschma, 2009), information science (Kim and Chang, 2010) and social psychology (Wölfer and Hewstone, 2017). With the development of social network theory, SNA has also been gradually introduced into the domain of safety assessment to analyze the relevance of risk factors from the perspective of relational embedding.…”
Section: Literature Reviewmentioning
confidence: 99%